(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Currently, a number of theoretical studies have looked into how Corporate Social Responsibility (CSR) is conceptualized and organized in developing nations like India, as well as how to raise awareness of the concept. This essay examines how the Companies Act of 2013’s implementation of corporate social responsibility (CSR) has affected corporate incentives, implications for resource availability, the provision of social goods, and implementation challenges. This paper’s goal is to explain the concept of corporate social responsibility (CSR) and examine how it has evolved in India by highlighting the laws that govern it and the CSR initiatives that Indian businesses have undertaken. This paper provides insightful recommendations for overcoming obstacles and ensuring successful implementation.